2021
DOI: 10.3389/fphar.2021.609702
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Myocardial Ischemia Reperfusion Injury Mechanism of Dried Ginger-Aconite Decoction Based on Network Pharmacology

Abstract: Dried ginger-aconite decoction (DAD) is a traditional Chinese medicine (TCM) formula that has been extensively used in the treatment of myocardial ischemia reperfusion injury (MI/RI). However, its specific mechanism against MI/RI has not been reported yet. Therefore, this paper studies the potential active components and mechanism of DAD against MI/RI based on network pharmacology and experimental verification. Sixteen active components of DAD were screened according to oral bioavailability and drug similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Oxidative stress injury is one of the important mechanisms of MI injury ( Xie et al, 2021 ). In order to determine whether YTC affects biochemical enzymes related to oxidative stress, we measured the levels of intracellular lipid peroxidation products (MDA) and antioxidant enzymes (SOD, GSH-Px and CAT).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress injury is one of the important mechanisms of MI injury ( Xie et al, 2021 ). In order to determine whether YTC affects biochemical enzymes related to oxidative stress, we measured the levels of intracellular lipid peroxidation products (MDA) and antioxidant enzymes (SOD, GSH-Px and CAT).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the role of flavonoids of O. falcata were investigated. The analysis of network pharmacology revealed the intricate interactions among drug components, disease targets, signaling pathways, and molecular mechanisms of TCMs [ 11 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has been widely used in China for thousands of years, and it has better therapeutic effects on various complicated disorders with few side effects [ 10 ]. Numerous clinical and experimental studies have demonstrated that Chinese medical prescriptions and herbal medicine extracts may play a therapeutic role in MIRI by exerting an anti-inflammatory and anti-apoptotic effect, maintaining calcium homeostasis, providing the clearance of oxygen free radicals, and avoiding platelet aggregation [ 11 , 12 , 13 , 14 ]. In addition, TCM extracts or mixtures possess more effective pharmacological activities than purified compounds due to their multiple components and targets [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several ingredients with high pharmacological activities, which can not fulfill the two conditions (OB ≥ 30%, DL ≥ 0.18), were also included according to the results of our previous qualitative analysis or other studies ( 16 ).…”
Section: Methodsmentioning
confidence: 99%